2005
DOI: 10.1088/0953-2048/18/5/026
|View full text |Cite
|
Sign up to set email alerts
|

Multifilamentary,in situroute, Cu-stabilized MgB2strands

Abstract: Transport critical current densities and n-values were measured at 4.2 K in fields up to 15 T on 7, 19, and 37-stack multifilamentary MgB 2 strands made using an in-situ route. Some strands included SiC additions (particle size ? 30 nm), while in others Mgrich compositions were used. Two basic multifilamentary variants were measured, the first had Nb filamentary barriers, the second had Fe filamentary barriers. All samples incorporated stabilizer in the form of Cu 101. Simple, one-step heat treatments were use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 24 publications
(47 reference statements)
0
49
0
1
Order By: Relevance
“…Work reported by others [6] has shown that the quality of the boron precursor influences MgB 2 superconducting properties. Figure 3 indicates the boron powder made in this study can be used to make MgB 2 wire with performance characteristics that equal or exceed those made with SB99 [4]. The curve of J c performance MgB 2 wire made with SMI 4% carbon-doped boron indicates that the wire maintains a current density of >10 5 A cm -2 up to magnetic field strengths of approximately 6 tesla.…”
Section: Analysis Of Mgb 2 Wires Made From Nano-sized Boron Powdermentioning
confidence: 81%
See 1 more Smart Citation
“…Work reported by others [6] has shown that the quality of the boron precursor influences MgB 2 superconducting properties. Figure 3 indicates the boron powder made in this study can be used to make MgB 2 wire with performance characteristics that equal or exceed those made with SB99 [4]. The curve of J c performance MgB 2 wire made with SMI 4% carbon-doped boron indicates that the wire maintains a current density of >10 5 A cm -2 up to magnetic field strengths of approximately 6 tesla.…”
Section: Analysis Of Mgb 2 Wires Made From Nano-sized Boron Powdermentioning
confidence: 81%
“…The wires were subsequently heat treated at 650-700°C to fully react the Mg and B. Critical current densities were measured by hysteresis [2] and transport methods [4] as previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…We find that the transport critical current of these wires increases significantly with the addition of metals that possess both large electron-electron interactions and long electron mean free paths, and not due to the filament morphology. In particular, the temperature dependence and magnitude of the Also, the insertion of thin barrier layers, similar to those used in the copper stabilized in situ MgB 2 multifilamentary wire fabricated by Sumption et al [17], will significantly reduce the alloy formation at the copper/filament interface in MgB 2 /Ga (20) wire and may also lead to improved transport currents. In addition, the relatively low T C at the MgB 2 particle surface is also limiting the supercurrent in these composites.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike HTS ceramics, however, supercurrent flow in polycrystalline MgB 2 is not significantly impeded by the grain boundaries due to the relatively long coherence length of the material [5,6] and the metallic nature of the grain boundaries [7]. These characteristics have allowed for the relatively rapid development of MgB 2 wire and tape with critical current densities (J C ) in the range of 10 4 to 10 6 A/cm 2 at 4.2K in modest magnetic fields ( < 4 Tesla ) by a number of groups worldwide [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand the research has been focused on the pinning issue and several doping procedures have been developed in order to improve the behaviour in magnetic field, most of them regarding the in-situ [2-5] even though works using the ex-situ do not lack [6]. On the other hand, the clear applicative prospect has prompted the development of techniques to produce multifilamentary wires [7][8][9][10] or cables [11,12]. After few years since the discovery of superconductivity in MgB 2 , long multifilamentary strands -of the order of kmhave been fabricated by Hyper Tech Research using the in-situ [13] and Columbus Superconductors using the ex-situ [9] way.…”
Section: Introductionmentioning
confidence: 99%